Elite swimmers' internal markers trajectories in ecological training conditions - Vacher, P.; Martinent, G.; Mourot, L.; Nicolas, M. (Scandinavian Journal of Medicine & Science in Sports, 2018)
This study examined the trajectories of elite swimmers` recovery-stress states and cardiac vagal-related markers during a three-month training period preceding the national championship and their within-person relationships with perceived control. Methods: A Multilevel Growth Curve Analysis (MGCA) approach was used with 21 male elite swimmers. Four waves of assessments of psychological (stress, recovery, perceived control) and physiological (heart rate variability, HRV) markers were completed during a three-month training preparation leading to a major competition. Results: Results of MGCA revealed: (a) a significant positive linear effect of time (i.e., linear increase over time) and a significant negative quadratic effect of time (i.e., inverted U shape over time) on perceived stress whereas the opposite pattern of results was observed for perceived recovery; and (b) a significant positive linear effect of time for nHRR60. Both at level 1 (within-person level of analysis) and 2 (between-person level of analysis), perceived control was: (a) positively associated with athletes` perceived recovery and parasympathetic markers (i.e., MeanRR; pNN50); and (b) negatively related to swimmers` perceived stress. Results also indicated that within-person interactions of perceived control with time reached significance for general recovery and HRV. Finally, within-person interaction of perceived control with squared time reached significance for subjective sport-specific and total stress. Conclusion: Overall, this study provided insights into the key role played by perceived control on both psychological and physiological markers related to recovery-stress states` levels during the three-month training period preceding the national championship.